Development of a Bio-barcode Assay for the Electrochemical Detection of a Cancer Protein Biomarker - Traynor, Sarah (My University, 2020)
There is a tremendous need for biosensing systems that can be operated at the point-of-care for disease screening and diagnostics and health monitoring. In spite of this, systems that offer the required analytical sensitivity and specificity in clinical samples, and are truly simple to operate using a sample-in-answer-out approach remain elusive. To address this challenge, the development and optimization of an electrochemical bio-barcode assay (e-biobarcode assay) that integrates biorecognition with signal transduction using molecular (DNA/protein) machines and signal readout using nanostructured electrodes is presented within this thesis. The e-biobarcode assay eliminates multi-step processing and uses a single step for analysis following sample collection into the reagent tube. Using this assay, a clinically-relevant performance for the analysis of prostate specific antigen (PSA) in undiluted and unprocessed human plasma: a log-linear range of 1 ng mL-1 – 200 ng mL-1 and a LOD of 0.385 ng mL-1 was achieved. The simplicity of the e-biobarcode assay offers a realistic solution for biomarker analysis at the point-of-care.